Impact of Teaching Cybersecurity Professional Courses for Students of Higher Learning Institutions: What Should the Society Expect? - Nkata, Anold S. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
The evolution of science, technology, and innovation (STI) characterized by digital transformation has significantly increased cybersecurity threats in socio-economic activities across the globe. The cybersecurity index of the global year 2024 outlines that the economy of developing countries will be affected by cyber criminals who are rapidly increasing worldwide. Globally, cybercriminals are constantly innovating their skills of attacking and hacking information systems. This study examined the problem in Tanzania by assessing the impact of teaching professional cybersecurity courses for students pursuing higher education who later graduate and live without employment. Findings reveal that the nation produces cybersecurity professionals who graduate yearly with sophisticated cybersecurity skills. The study recommends that the government should take precautions to protect itself economically and set a professional cybersecurity policy of identifying and registering students graduating in the field of cybersecurity. Moreover, public training and awareness of cybercrime Acts, and infringements are highly needed for the citizens. This study serves as a knowledge gap for education policymakers, education institutions, and the government to take measures to safeguard the nation’s future digital economy by enhancing cybersecurity awareness among the citizens through the provision of education using mass media and training via various education platforms.